Characterization of a novel reassortment Tibet orbivirus isolated from Culicoides spp. in Yunnan, PR China. (8th September 2021) - Ren, Nanjie; Wang, Xiaoyu; Liang, Mengying; Tian, Shen; Ochieng, Christabel; Zhao, Lu; Huang, Doudou; Xia, Qianfeng; Yuan, Zhiming; Xia, Han
Abstract : Orbiviruses are arboviruses with 10 double-stranded linear RNA segments, and some have been identified as pathogens of dramatic epizootics in both wild and domestic ruminants. Tibet orbivirus (TIBOV) is a new orbivirus isolated from hematophagous insects in recent decades, and, currently, most of the strains have been isolated from insects in PR China, except for two from Japan. In this study, we isolated a novel reassortment TIBOV strain, YN15-283-01, from Culicoides spp. To identify and understand more characteristics of YN15-283-01, electrophoresis profiles of the viral genome, electron microscopic observations, plaque assays, growth curves in various cell lines, and bioinformatic analysis were conducted. The results indicated that YN15-283-01 replicated efficiently in mosquito cells, rodent cells and several primate cells. Furthermore, the maximum likelihood phylogenetic trees and simplot analysis of the 10 segments indicated that YN15-283-01 is a natural reassortment isolate that had emerged mainly from XZ0906 and SX-2017a.